Enriching of bread for patients with diabetes by mineral substances - Drobot, Vira; Shevchenko, Anastasiia; Bondarenko, Yuliia (My University, 2016)
The work is devoted to the research of the impact of calcium, magnesium, zinc, iron citrates and their mixture on bread for diabetics. The effect of citrates on the technological process of making bread and quality of finished products has been set set.
Keywords: citrates of metals; fructose; mineral substances; bread; diabetes; technology; цитрати металів; фруктоза; мінеральні речовини; хліб; діабет; технологія; кафедра технології хлібопекарських і кондитерських виробів; цитраты металлов; минеральные вещества; хлеб; диабет; технология